PENGARUH SHOPPING LIFETYLE, FASHION INVOLVEMENT, DAN HEDONIC SHOPPING MOTIVATION TERHADAP IMPULSE BUYING - Suhartini, Yuniar Indah; Rodhiyah, Rodhiyah; Listyorini, Sari (Departemen Administrasi Bisnis, FISIP Universitas Diponegoro, 2016)
The development of retail and caused consomer behavior changes in the spending. Consumers now it is not just go shopping due to shooping needed it but due to emotional feelings. This research specifically discusses consumers on Matahari Departement store in Semarang City. This report aims to review the influence of shooping lifestyle, fashion involvement and hedonic shopping motivation towards impulse buying of the consumer of Matahari Departement Store in Semarang City. Type eksplanatory research. Data collection techniques using purposive sampling with a sample of 100 consumers. Quantitative data were analyzed using SPSS version 17. Data were analyzed through the validity, reliability, crosstab, product moment correlation, coefficient of determination, simple linear regression, multiple linear regression, t test and F test. The results show that impulse buying is high. Then shopping lifestyle is quite high, shopping lifestyle has a moderate influence on the impulse buying (19.6 percent) as well as the significant and positive impact on impulse buying (0.358). Fashion involvement is high, fashion involvement has a high influence on the impulse buying (37.6 percent) as well as the significant and positive impact on impulse buying (0.543). Hedonic shopping motivation is quite high, hedonic shopping motivation has a moderate effect (30.4 percent) as well as the significant and positive impact on impulse buying (0,702). Shopping lifestyle, fashion involvement and hedonic shopping motivation to have a strong influence on impulse buying (48.5 percent). In conclusion shopping lifestyle, fashion involvement and hedonic shopping motivation higher so impulse buying higher. Suggested Matahari Department Store improve their services, comfort, products diversity, product quality and products provided should continue to follow the trend of fashion. In addition Matahari Departement Store in its business of doing business must be accordance with ethics of business. The consumers must be more careful and wise in the conducting any activity shopping so they do not feel remorse after shopping.